2020
DOI: 10.1111/jac.12390
|View full text |Cite
|
Sign up to set email alerts
|

Root and shoot responses of upland New Rice for Africa varieties to fluctuating soil moisture conditions as affected by different levels of nitrogen fertilization

Abstract: Drought cycling and soil re-watering trends due to intermittent rainfall patterns are key stress factors that influence rice growth and yield under upland cultivation conditions. However, upland rice adaptation responses to fluctuating soil moisture conditions remain poorly understood. This study investigated root and shoot responses of upland New Rice for Africa (NERICA) varieties to episodic drought and re-watering during growth. We examined root and shoot growth of NERICA 1 and NERICA 4 compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For instance, (Suralta et al., 2010) demonstrated that a rice variety with a well‐developed root system exhibited a rapid recovery of photosynthetic ability during specific waterlogged periods following drought, resulting in increased shoot dry matter production. Additionally, according to (Menge et al., 2020), enhanced root development during drought can contribute to shoot growth during subsequent flooded periods, when sufficient water is available. These findings support our hypothesis that the enhanced S‐type LR development in the our1 mutant contributed to shoot growth through increased water uptake ability as a corresponding response to sufficient water availability between drought periods.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, (Suralta et al., 2010) demonstrated that a rice variety with a well‐developed root system exhibited a rapid recovery of photosynthetic ability during specific waterlogged periods following drought, resulting in increased shoot dry matter production. Additionally, according to (Menge et al., 2020), enhanced root development during drought can contribute to shoot growth during subsequent flooded periods, when sufficient water is available. These findings support our hypothesis that the enhanced S‐type LR development in the our1 mutant contributed to shoot growth through increased water uptake ability as a corresponding response to sufficient water availability between drought periods.…”
Section: Discussionmentioning
confidence: 99%
“…Rice ( Oryza sativa L.), an essential crop for global food security, requires massive amounts of fresh water for irrigation. Various water‐saving practices have been designed, such as alternate wetting and drying (Bouman & Tuong, 2001; Carrijo et al., 2017; Menge et al., 2020; Mishra & Salokhe, 2010), and controlled soil drying during grain filling (Yang & Zhang, 2006; Yang et al., 2003). However, yield penalties appear unavoidable.…”
Section: Introductionmentioning
confidence: 99%